(untitled) (NAU Journal of Technology and Vocational Education, 2026)
Entrepreneurial intentions among undergraduate students remain a critical concern for policymakers and educators seeking to embed entrepreneurship within higher education curricula. Grounded in Bandura’s Social Cognitive Theory and the Theory of Planned Behaviour, this study investigated entrepreneurial self-efficacy and risk-taking propensity as antecedents of entrepreneurial intentions among final-year technology and vocational education undergraduates in public universities in South-East Nigeria. A predictive correlational design was employed, with data drawn from a census of 326 final-year undergraduates during the 2024/2025 academic session. Confirmatory factor analysis indicated an acceptable fit of the measurement model, and the retained constructs demonstrated satisfactory reliability (CR = .697–.867; α = .671–.865), supporting the adequacy of the measures for subsequent analyses. Three hypotheses were tested at α = 0.05 using simple and multiple linear regression analyses, executed through the SPSS PROCESS Macro (Version 4). Findings revealed that both entrepreneurial self-efficacy (β = 0.577, p < .05) and risk-taking propensity (β = 0.211, p < .05) significantly and positively predicted entrepreneurial intentions. Jointly, the two variables accounted for a significant proportion of variance in entrepreneurial intentions, with entrepreneurial self-efficacy emerging as the relatively stronger antecedent. These results underscore the salience of psychological capital in shaping entrepreneurial career orientations among technology and vocational education students. Thus, we recommend that entrepreneurship education programmes integrate experiential and simulation-based learning pedagogies designed to strengthen students’ self-efficacy and cultivate adaptive risk orientation.